DAMAGE ASSESSMENT AND DIAGNOSIS – Sé Nova, Coimbra - Gonçalves, T. D. (2014)
This report concerns the Sé Nova, Coimbra, which was used as a case-study of the EU project COMPASS. It focuses the assessment of damage, diagnosis and advice for repair of salt decay anomalies. It concludes that repair of the damaged plasters could be done with a lime-mortar, as similar as possible to the existing one, namely in its high capillary absorption. A paint that does not constitute a barrier to the incoming salt solutions should also be used.